BEST APPROXIMATION AND BEST COAPPROXIMATION IN METRIC LINEAR SPACES - Narang, T.D.; Gupta, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2016)
In this paper, we discuss best approximation and best coapproximation in metric linear spaces. We obtain some results on the characterizations, existence and uniqueness of elements of best approximation and best coapproximation in metric linear spaces. We also study single-valuedness and linearity of metric projection and metric coprojection maps.